Actualistic taphonomic study of the rodents digested by the Achala culpeo fox (Lycalopex culpaeus smithersi) in the highlands of central Argentina - Coll, Daiana Geraldine (2021)
We present the first actualistic study of the rodents consumed by the South American foxLycalopex culpaeus smithersi (Achala culpeo fox), a subspecies of the culpeo fox that is endemicto the highlands of central Argentina. We provide a taphonomic characterization of this canidbased on digested micromammal bones, and compare it to other carnivores. We studied over 1000bones derived from 83 scats collected in Quebrada del Condorito National Park, Córdobaprovince, Argentina, corresponding to caviomorph and myomorph rodents. Galea leucoblepharawas the main prey (59.8% MNI, 93.1% biomass). Average relative abundance for the totalassemblage was 26.7. Cranial and, to a lesser extent, proximal limb bones were the most abundantelements. A high degree of breakage was observed in cranial elements and, to a lesser extent, inlimb bones. A high proportion of heavy and extreme digestion was inferred, while some elementsbear light or no digestion traces at all. Overall, the Achala culpeo fox fits best with othermammalian carnivores in the category of extreme modification, and shows types and proportionsof taphonomic attributes similar to other South American mammalian predators. These resultscontribute to the understanding of regional taphonomic processes and of digestivemodifications by Lycalopex foxes generally, and are thus relevant to interpreting the presence of micromammal remains in the archaeological and palaeontological recordsand the impact of these foxes in their formation.